2016
DOI: 10.1093/nar/gkw1284
|View full text |Cite|
|
Sign up to set email alerts
|

Rapid decay of engulfed extracellular miRNA by XRN1 exonuclease promotes transient epithelial-mesenchymal transition

Abstract: Extracellular vesicles (EVs) have been shown to play an important role in intercellular communication as carriers of DNA, RNA and proteins. While the intercellular transfer of miRNA through EVs has been extensively studied, the stability of extracellular miRNA (ex-miRNA) once engulfed by a recipient cell remains to be determined. Here, we identify the ex-miRNA-directed phenotype to be transient due to the rapid decay of ex-miRNA. We demonstrate that the ex-miR-223-3p transferred from polymorphonuclear leukocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Furthermore, XRN1 and XRN2 play a role in miRNA stability (3436), especially if miRNA is taken up from the extracellular space (37). XRN1 also regulates accumulation of viral dsRNA (38).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, XRN1 and XRN2 play a role in miRNA stability (3436), especially if miRNA is taken up from the extracellular space (37). XRN1 also regulates accumulation of viral dsRNA (38).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that low levels or activity of FOXO1 have a close relationship with tumorigenesis . FOXO1 silencing is related to suppressed EMT in A549 lung adenocarcinoma epithelial cells, which is evidenced by decreased epithelial markers (E‐cadherin) and enhanced mesenchymal markers (SNAIL, SLUG) . Helicobacter pylori infection is the major risk factor for gastric cancer.…”
Section: Foxo1 and Carcinogenesismentioning
confidence: 96%
“…34,35 FOXO1 silencing is related to suppressed EMT in A549 lung adenocarcinoma epithelial cells, which is evidenced by decreased epithelial markers (E-cadherin) and enhanced mesenchymal markers (SNAIL, SLUG). 36 Helicobacter pylori infection is the major risk factor for gastric cancer. In human gastric cancer epithelial cells, phosphorylated FOXO1 (pFOXO1), the inactive form of FOXO1, is highly expressed in the cytoplasm rather than the nucleus, revealing that the disruption of FOXO1 subcellular location might induce early gastric carcinogenesis among Helicobacter pylori-infected patients.…”
Section: Foxo1 and Carcinogenesismentioning
confidence: 99%
“…Although they are 24-25 nucleotides approximately the length of miRNAs or siRNAs, immRNAs form stable hairpins with stable blunt duplex ends [6]. So they may not be easily degraded by 5 0 exonuclease Xrn1 and 3 0 exonuclease exosome complex [46,47]. They are also not like the long double-stranded RNA which could be cleaved by Dicer into 21-23mer siRNA.…”
Section: Discussionmentioning
confidence: 99%